Analisis Putusan Hakim Pengadilan Agama Kabupaten Cirebon pada Prosedur Eksekusi Sita Jaminan Perkara Murabahah - Abdullah, Fadli Daud; Sururie, Ramdani Wahyu; Mukhlas, Oyo Sunaryo (CV. Strata Persada Academia, 2023)
This research analyzes the decision of the Sumber Religious Court of Cirebon Regency in the procedure for executing the confiscation of sharia mortgage rights in the murabahah case Number 2008/Pdt.G/2020/PA.Sbr. This research pays attention to the role and actions of religious courts in handling execution cases, assessing debt collateral, and protecting the rights of debtors and creditors in sharia economic cases. The author uses a qualitative method with a normative approach. The analyzes primary data such as the judge's decision and related documents and analyzes secondary data as a source of information which includes literature study. This execution process involves the State Property and Auction Services Office and may face challenges from debtors or third parties. The case study of case Number 2008/Pdt.G/2020/PA.Sbr shows that the execution mechanism for the auction of mortgage rights was carried out outside the Sumber Religious Court, Cirebon Regency, without a court execution order. The judge considers it according to the applicable legal basis. As a result, the Plaintiff's lawsuit was rejected because of the implementation of the auction by Bank BRI Syariah.Tbk Cirebon Branch Office was deemed to be in accordance with the law. Default by the Customer is the main reason for this decision.